Implementation of Islamic Religious Education Learning in an Independent Curriculum Perspective - Aluk Maknunah; Abdul Muis (Program Pascasarjana Universitas Ibrahimy, 2023)
Islamic Religious Education the subject that emphasizes aspects of improving the behaviour of students had a responsibility to solve these problems, because of that PAI was expected to be able to motivate students to do good and leave everything that was prohibited by religion, the implementation of Islamic Religious Education gets space which was sufficient to be developed especially after the implementation of the independent curriculum, school managers were allowed to carry out learning innovations according to the interests and talents of students, based on this thought there was research on the Implementation of PAI in SD Asy-Syafaah (Full Day School), the focus of this research is 1 ) how was the implementation of PAI learning in the perspective of an independent curriculum 2) What were the supporting and inhibiting factors in the implementation of PAI learning. This study used a qualitative approach with descriptive methods, while data collection was carried out through interviews, observation and documentation. students can achieve the learning objectives of PAI based on the achievement of KKM PAI scores and students' memorization of the Koran was quite successful as well as the religious behaviour of students in their daily lives, and it provides sufficient space to develop students' interests and talents as mandated by the independent curriculum 2) in this implementation there were several supporting factors such as the availability of sufficient facilities and inhibiting factors including the input of students who were not yet adequate.